De exilio de la patria al exilio del ‘ser’ Desterritorialización y desemiotización del emigrado-exiliado: Desterritorialización y desemiotización del emigrado-exiliado - Cifuentes-Aldunate, Claudio (Diálogos Latinoamericanos, 2023)
The present study proposes an analysis of the subject of exile represented in literature and film within the Hispanic culture. We consider the symbolic character of exile and de-exile, as well as the different ways of living the ‘exile experience’. This is materialized in an ad hoc narrative path or process that draws the sequence of exile. We show different ways of assuming this trauma, and how this produces different modalities of subject.